Design of Cloud Computing System–Based Pollution Distribution Map in Iraq - Mohammed Azher Therib; Laith Awda Kadhim Mayyahi; Zahraa Emad Fadel; Laith Ali Abdul-Rahaim (Journal of Electrical and Computer Engineering)
Air pollution is widespread in the world and is considered one of the most important risk factors in Iraq, especially as a result of the lack of a green belt surrounding cities and the many causes of pollution, including traffic congestion, the spread of gas power plants and other causes of pollution. The most common factors of pollution in the air are the spread of gases that are harmful to human health, including monoxide, carbon dioxide (CO2), ozone and the spread of dust, which directly affects human health. A smart system has been proposed to measure levels of pollutants, of which carbon monoxide (CO), dioxide and dust are at the forefront. Several cities, including Baghdad, Karbala, Najaf and Hilla, were chosen to measure the percentage of disparity between pollutants in these cities, determine the percentage of CO2 on Google maps for these cities and update the data instantly by sending the data via the cloud computing. The implemented system consists of an Arduino Uno, a (MG811) sensor to measure CO2, a (MQ-2) sensor to CO and a (DSM501A PM2.5) sensor to measure air quality and the percentage of dust in the atmosphere. The data was also sent via the (Time4vps) cloud computing so that the data were updated instantly. The results obtained showed a difference in the percentage of pollutants between cities and different periods during one day and in one city. The proposed system is very successful to ministry of health if it is implemented in all cities and all the regions of cities around the country because it gives the alert to make all health organizations ready to receipt the higher number of patients in the emergency cases.